Sim on Bol ivar : South American liberator - Angell, Hildegarde (New York : W.W. Norton & Company, Inc., 1930)
"Miss Angell's book ... represents a fresh reading of Bol ivar's correspondence, and of the many chronicles and memoirs of his companions-in-arms; and by liberal quotation from these eye-witnesses she has given a faithful and lifelike picture of the Liberator and his environment. Bol ivar remains the indomitable warrior, tamer of men and forger of nations, but through all the biographer's enthusiasm peer the human frailties of her subject as well."--C.H. Haring.
Includes index.
"Primary sources": pages 275-279; "Bibliography of secondary works": pages 281-284.
Also issued online.
NLJCols20082021
Keywords: Bol ivar, Sim on, -- 1783-1830.; Bol ivar, Sim on, -- 1783-1830; Heads of state -- Venezuela -- 19th century; South America -- History -- Wars of Independence, 1806-1830.; Venezuela; South America; Heads of state; 1800-1899; History